The Impact of Online Learning on Students’ Interest in Chemistry Education Study Program - Noviza Rizkia; Khairunnisak Khairunnisak; Maulidya Maulidya (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
The Covid-19 pandemic has caused the teaching and learning process to be conducted online as a substitute for classroom learning. This study aims to determine the effect of online learning on student interest in the Chemistry Education program at UIN Ar-Raniry Banda Aceh, Indonesia. This research is qualitative research with a qualitative descriptive method with a sample of 40 students. The data was collected through distributing questionnaires within three days to obtain information about the impact of distance learning during the covid-19 pandemic on student interest in the chemistry education program. The results of data analysis showed that 44.33% of students had a good interest in online learning. It means that students' interest in learning is not good for online learning.